Rulers and victims : the Russians in the Soviet Union - Hosking, Geoffrey A. (Belknap Press of Harvard University Press, 2006)
Russians regarded the Soviet Union as their country, but that did not mean they were entirely happy with it. In the end, in fact, Russia actually destroyed the Soviet Union. How did this happen, and what kind of Russia emerged? Historian Hosking explores what the Soviet experience meant for Russians. Messianism--the idea rooted in Russian Orthodoxy that the Russians were a "chosen people"--Was reshaped by the communists into messianic socialism, in which the Soviet order would lead the world in a new direction. Hosking analyzes how the Soviet state molded Russian identity; the dislocations resulting from collectivization and industrialization; the relationship between ethnic Russians and other Soviet peoples; the effects of World War II on ideas of homeland and patriotism; and leadership and the cult of personality. At the heart of this work is the fundamental question of what happens to a people who place their nationhood at the service of empire.--From publisher description